Analis Skala Ekonomis da Efisiensi Penggunaan Faktor-faktor Produksi pada Usaha Perkebunan Kopi Arabika di Desa Satra, Kecamatan Kintamani Kabupaten Bangli - Adriyansayah, Danny; Marhaeni, Anak Agung Istri Ngurah (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 2, Februari 2016 (pp. 115 - 285), 2017)
The purpose of this study are to analyze ; 1 ) s simultaneously and 2) to analyze the partial effect of the use of production factors land, use of fertilizer and labor to Arabica C offee production and 3) to analyze the economies of scale and 4) analyze the efficiency of production factors in the plantation business of A rabica C offee in the Desa Satra of Kintamani Bangli Regency. The type of data in this study is  quantitative and qualitative data with the primary and secondary data sources. Data analysis techniques used in this research is the analysis techniques of Cobb-Douglass, economies of scale and economic efficiency. Respondents in this study amounted to 84 peoples a sample of 501 farmers in 10 Subak Abian calculated using the Slovin’s formula. Determination of the amount of sample in each Subak Abian determined by the proportionate stratified random sampling method, and using accidental sampling method. The results showed that the variable land area (X1), the use of fertilizers (X2) and labor (X3) simultaneously and partially positive and significant impact on the amount of production (Y) to the plantations of Arabica Coffee in the village of Satra, Kintamani Bangli Regency.  Economies of scale test in a state of increasing returns of scale and the efficiency of use of production factors have not been efficient. It is recommended that farmers Arabica Coffee plantation in the village of Satra continuously can increase productivity by making use of all factors of production are owned optimally.
Keywords: Jumlah Produksi; Skala Ekonomis; Efisiensi Faktor-Faktor Produksi